The warrior's way [videorecording (DVD)] - Lee, Sngmoo; Huston, Danny, 1962-; Rush, Geoffrey, 1951-; Bosworth, Kate, 1983-; Chang, Tong-gŏn, 1972- (20th Century Fox Home Entertainment, 2011)
A Samurai warrior-assassin is forced to hide in a small Western town in the American Badlands after refusing a mission.